Analysis and design of geotechnical structures - Fernandes, Manuel Matos (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2020)
"This takes Masters students from basic soil mechanics to theory and methods and geotechnical engineering practice. Basic principles and analysis are given with design to Eurocode 7, covering advanced theory, geotechnical characterization and sophisticated applications. With exercises, and a solutions manual for adopting course instructors"--
OCLC-licensed vendor bibliographic record.
Keywords: Geotechnical engineering -- Textbooks